Tryptophan-rich diet is negatively associated with depression and positively linked to social cognition - Reuter, Martin; Zamoscik, Vera; Plieger, Thomas; Bravo, Rafael; Ugartemendia, Lierni; Rodriguez, Ana Beatriz; Kirsch, Peter (Nutrition research, 2021)
The essential amino acid tryptophan (TRP) is discussed as a potential protective factor for physical and mental health. Besides positive effects via the microbiota of the gut on many physiological processes, TRP is the precursor of the neurotransmitter serotonin (5-HT), thereby playing a role for affective disorders. The present study investigated the effects of a TRP-rich diet on depressiveness and on one of its endophenotypes, impaired social cognition, in a population based sample. N=482 subjects participated in an online study, assessing the ability to properly recognize emotional states from the eye region of faces (Reading the Mind in the Eye Test, RMET) and asking for subjective ratings of condemnability in a moral judgment task. Moreover, the habitual TRP intake was measured. It was hypothesized that a low-TRP diet is associated with higher depressiveness and worse performance in the social cognition tasks. The main hypotheses could be supported. However, contrary to the expectations, the effect of TRP on social cognition was not mediated by depressiveness. Results show that a tryptophan-rich diet is a potential protective factor against depression and is positively related to functioning in social cognition.
Gesehen am 04.05.2021